Increase of efficiency of acceleration of the test electron bunch by sequence of electron bunches in the dielectric resonator - Markov, P.I.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2018)
Results of numerical simulation of the test bunch acceleration by relativistic electron bunch sequence in the cylindrical dielectric resonator of terahertz frequency range are provided. If the bunch spacing equals to the electromagnetic field wavelength in structure and the test bunch follows the last bunch of sequence, the step energy growth of the accelerated test bunch with increase in number of drive bunches is observed. To approach step dependence to linear and, thus, to avoid cases when the increase in drive bunches number does not lead to energy growth of test bunch, it is necessary to arrange bunches of sequence at distance not smaller resonator lengths. Bunch repetition period has to be multiple of the inverse to resonant frequency of structure.